2010
DOI: 10.1089/jwh.2009.1434
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Therapy and Risk of Lung Cancer: A Meta-Analysis

Abstract: Overall, the findings of this meta-analysis do not support the hypothesis that there is a link between HT use and lung cancer risk. Our findings should be evaluated in further prospective cohort studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Our findings suggest that exogenous hormones may have a protective effect in lung cancer development consistently with a meta-analysis of previously published case–control studies showing a reduced lung cancer risk in HRT ever users (OR 0.81; 95% CI 0.68–0.97) (Oh et al , 2010). …”
Section: Discussionsupporting
confidence: 88%
“…Our findings suggest that exogenous hormones may have a protective effect in lung cancer development consistently with a meta-analysis of previously published case–control studies showing a reduced lung cancer risk in HRT ever users (OR 0.81; 95% CI 0.68–0.97) (Oh et al , 2010). …”
Section: Discussionsupporting
confidence: 88%
“…Postmenopausal patients who received hormone replacement therapy (HRT) for more than 10 years had a higher risk of developing LC [27]. Nevertheless, the relationship between estrogen and LC is unclear and has not been examined in patients with EGFR -mutant NSCLC [27,28,29,30]. Interaction between the ER and EGFR has been described, and a preclinical trial suggested that the development of both BC and LC may be related to the ER pathway.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…A protective effect of menopausal hormone therapy (MHT) and oral contraceptive (OC) use has been proposed in a pooled analysis [29], and reduced lung cancer risks in MHT users respect to never users have been found in a meta-analysis of case–control studies [30]. However, a meta-analysis including studies with diverse design found instead a positive association of MHT use with lung cancer in specific subgroups of subjects [31], and most studies on OC administration found no association [29].…”
Section: Introductionmentioning
confidence: 99%